Social regulation and shifting institutional culture in higher education: A reflective account of a Faculty of Education - Small, R; Smith, J; Williams, C; Fataar, A (South African Journal of Higher Education, 2011)
This article addresses the question: To what extent did social regulation impact on the institutional culture of a faculty of education at a South African public higher education institution over a ten year period from approximately 1998 until 2007? We engaged in systematic reflections about our experiences as members of the Faculty of Education, University of the Western Cape and analysed relevant Faculty documents. We used the notions of repressive and sovereign power to understand how the Faculty mediated social regulation. We found that there were three discrete periods, each characterised by a distinctive institutional culture. The late 1990s was simultaneously contrarian to, and compliant with, regulatory powers; 2000–2003 was a survivalist period; and from 2004–2007 the Faculty actively moderated the repressive powers in its functional environment. We conclude that the Faculty’s sovereign agency that re-emerged between 2004 and 2007 serves as basis for developing a rigorous research-informed teacher education platform.